2018
DOI: 10.1101/438176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamic proteome of influenza A virus infection identifies M segment splicing as a host range determinant

Abstract: A century ago, influenza A virus (IAV) infection caused the 1918 flu pandemic and killed an estimated 20-40 million people. Pandemic IAV outbreaks occur when strains from animal reservoirs acquire the ability to infect and spread among humans. The molecular details of this species barrier are incompletely understood. We combined metabolic pulse labeling and quantitative shotgun proteomics to globally monitor protein synthesis upon infection of human cells with a human-and a bird-adapted IAV strain. While produ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 86 publications
(99 reference statements)
3
12
0
Order By: Relevance
“…We have recently shown that replication of the avian A/Mallard/439/ 2004 virus in A549 cells is attenuated by three orders of magnitude at 72 h.p.i. in comparison to A/Panama/2007/99 42,43 . We were able to demonstrate that both viruses enter A549 cells with similar efficiency, and that mRNA from both virus strains accesses the translational machinery with comparable efficiency.…”
Section: Resultsmentioning
confidence: 94%
“…We have recently shown that replication of the avian A/Mallard/439/ 2004 virus in A549 cells is attenuated by three orders of magnitude at 72 h.p.i. in comparison to A/Panama/2007/99 42,43 . We were able to demonstrate that both viruses enter A549 cells with similar efficiency, and that mRNA from both virus strains accesses the translational machinery with comparable efficiency.…”
Section: Resultsmentioning
confidence: 94%
“…In addition to HA receptor binding and stability, other adaptive properties contributing to influenza virus transmission include polymerase activity, virus morphology, and resistance to host-based restrictions to replication ( Mänz et al, 2012 ; Bogdanow et al, 2019 ; Long et al, 2019a ). Such adaptations may also be needed for swine gamma viruses to adapt highly efficient airborne transmissibility in ferrets.…”
Section: Discussionmentioning
confidence: 99%
“…In targeting the virus–host interaction, there is an emerging need of tools that could early identify those compounds, not primarily designed for their antiviral action, identifiable by in silico approaches ( Gordon et al, 2020b ), which alone or in combination can provide clinical efficacy ( Mina et al, 2016 ; Cheng et al, 2018 ; Bogdanow et al, 2019 ; Panja et al, 2019 ; Gordon et al, 2020b ). There are known advantages of in silico modeling of the action of therapeutic agents on known diseases through agent-based modeling ( Mao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%